Results of the PRECISION study: Could an answer be given to the question of how safe coxibs versus traditional NSAIDs are in treating patients at high risk for cardiovascular events? - E. V. Dovgan (Современная ревматология, 2017)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the most prescribed drugs worldwide and, like any medication, can cause adverse drug reactions. Since NSAIDs belonging to the group of coxibs, are quite commonly used in clinical practice now, the study of the safety of this class of drugs is given the highest priority. The paper analyzes a largest-scale PRECISION study of the safety of NSAIDs, the aim of which was to assess the cardiovascular safety of celecoxib versus that of ibuprofen and naproxen in patients with osteoarthritis and rheumatoid arthritis